Al-Quran Literacy and Sharia Business Mentoring: Young Entrepreneurial Candidates at SMK Muhammadiyah 4 Sragen - Saputro, Triyono Adi (PASAI : Jurnal Pengabdian kepada Masyarakat, 2025)
This Community Service Activity (PKM) aims to improve Quran literacy and understanding of sharia business for young entrepreneurs at SMK Muhammadiyah 4 Sragen, addressing the low national sharia financial literacy index. The implementation was carried out through site observations, lectures by experts, and interactive discussions and question-and-answer sessions with case study simulations from September to October 2025 in the school hall. The results showed a 30% increase in understanding (pre-post test), awareness of the integration of Quranic values in business ethics (60% of participants), and the development of Islamic business ideas such as mudharabah crowdfunding. This activity bridges the spiritual-economic dichotomy, creating a holistic mentoring model for Islamic-based vocational schools, with broad implications for the regional Islamic entrepreneurship ecosystem and contributions to SDGs 4, 8, and 9.